(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mansyur, Karti PMH, Abdullah L, Husni A, Lestari P. 2019. Genetic diversity of mutant napiergrass using Expressed Sequence Tag Simple Sequence Repeat (EST-SSR). Biodiversitas 20: 2403-2409. Napiergrass is one of the tropical grasses which has a very important role in developing ruminant livestock, its productivity is high and its nutritional content is quite good. Plant breeding to produce new varieties that have better productivity continues. One of them is through mutation breeding and in vitro culture. The purpose of this research was to look at the genetic diversity among napiergrasses using the Expressed Sequence Tag Simple Sequence Repeat (EST-SSR). This study used 14 SSR molecular markers. The results showed that mutant DNA of napiergrass can be clearly amplified by all the EST-SSR primers used. The average number of alleles was 4.57, the average frequency of the main allele was 42%, and the average value of gene diversity was 0.66. While the PIC average value was 0.60. There were five markers that were very informative and have PIC values ??above 0.7, among others, namely ICMP3045, ICMP3018, PSMP2090, PSMP2209, and PSMP2019. Phylogenetic analysis shows that 37 numbers of napiergrass mutants split into two main clusters at a coefficient of 0.56. The first cluster consists of 26 lines while the second cluster consists of 11 mutants. The parent napiergrass is in the first cluster. There are two pairs of mutants that have the same diversity, namely R20-11 with R 20-20-3 and R100-1 with R100-3.